EFISIENSI PENGGUNAAN Trichoderma sp UNTUK MENGENDALIKAN PENYAKIT LAYU FUSARIUM (Fusarium oxysporium) DAN PERTUMBUHAN BIBIT TANAMAN PISANG - Bukhari Bukhari; Nuryulsen Safridar (Universitas Lancang Kuning, 2018)
This research was conducted in Pante Cermin, Padang Tiji Subdistrict, Pidie District. in March to August 2015, with the aim to know the use efficienci of Trichoderma sp on the growth of several types of Banana seedlings (Musa Paracica L.) This research using Randomized Block Design (RAK) factorial pattern with the factors studied is the type of banana and trichoderma dose . Both factors consist of 4 levels: Banana Barangan (J1), Ambon banana (J2), Banana King (J3) and Geupok banana (J4). While the dose of Tricoderma sp is: TO = 0 g / seeds T1 = 15 g / seeds T2 = 30 g / seedlings and T3 = 45 g / seedlings. So there are 16 treatment combinations and repeated 3 times, which resulted in 48 experimental units.To determine the influence of each treatment and its interaction on the growth of banana seedlings, the analysis of variance (Test F) and continued with the test of Beda Nyata Jujur (BNJ) at 5% level.The results showed that the growth of good banana seedlings among 4 species studied was shown by Barangan bananas, but not unlike bananas. However, trichoderma administration until the age of 4 months has not shown the growth and intensity of different attacks. So it should be extended the study period to 6 months. After 6 months of research there has been a difference in growth and intensity of attack, where the intensity of the greatest attack is shown by T0 (without trichoderma). Medium intensity of smallest attack is shown by T3 (Dose trichoderma sp 45 gr / banana seedlings). The type of banana does not affect the growth and intensity of fusarium wilt attack. and the interaction of these two factors had no significant effect on the growth of banana seedlings and the intensity of Fusarium wilt disease.